Care in the Home for the Management of Chronic Heart Failure: Systematic Review and Cost-Effectiveness Analysis. (July 2015) - Fergenbaum, Jennifer; Bermingham, Sarah; Krahn, Murray; Alter, David; Demers, Catherine
Abstract : Background: The objective of this study was to determine the effect of care in the home (CHM) compared with usual care (UC) in patients with chronic heart failure (CHF) on clinical outcomes and healthcare use including a cost-effectiveness analysis. Methods: A systematic literature search on MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, the Cochrane Library, as well as Centre for Reviews and Dissemination was conducted to identify randomized controlled trials comparing CHM with UC in CHF. The randomized controlled trials meeting inclusion criteria were meta-analyzed by outcome, and the quality of evidence for each outcome was evaluated using Grading of Recommendations Assessment, Development, and Evaluation system. A cost-effectiveness model was developed to estimate costs and quality-adjusted life years. Results: Six randomized controlled trials were identified from 1277 citations. Care in the home was predominately provided by a single health professional consisting of nurse-led education of varying duration and frequency. One study included pharmacist-led CHM. Care in the home showed a decreased risk for all-cause mortality and hospitalizations combined (risk ratio, 0.88; 95% confidence interval [CI], 0.80–0.97), but not all-cause mortality alone (risk ratio, 0.92; 95% CI, 0.81–1.04). Care in the home resulted in fewer hospitalizations (mean difference, −1.03; 95% CI, −1.53 to −0.53) and fewer emergency department visits (mean difference, −1.32; 95% CI, −1.87 to −0.77). Quality of life also improved with CHM delivered by nurses. Critical appraisal of the quality of evidence suggests uncertainty in the estimates for a number of outcomes. Care in the home resulted in a savings of 10, 665 and a gain of 0.11 quality-adjusted life years compared with UC. Conclusions: In conclusion, the beneficial effect of CHM in CHF is by reducing mortality and hospitalizations combined. Care in the home in CHF seems to be more effective and less costly compared with UC.